Generic Reclassification of Limonius Eschscholtz, 1829 (Elateridae: Dendrometrinae) sensu Candèze 1860 of the World - Etzler, Frank E. (Zootaxa, 2019)
The genus Limonius Eschscholtz, 1829 was last treated as a whole by Candèze (1860). Since then, members have been placed in eight other genera: Cidnopus Thomson, 1859; Gambrinus LeConte, 1853; Elathous Reitter, 1890; Kibunea Kishii, 1966; Limoniscus Reitter, 1905; Nothodes LeConte, 1861; Pheletes Kiesenwetter, 1858; and Solskyana Dolin, 1978. Based on the examination of adult and larval characters, five genera are recognized: Elathous Reitter, 1890; Gambrinus LeConte, 1853; Limonius Eschscholtz, 1829; Pheletes Kiesenwetter, 1858; and Tetralimonius new genus. Limoniscus Reitter, 1905 and Sichuanelater Platia and Gudenzi, 2006 are new synonymies of Gambrinus LeConte, 1853; Micrathous Lane, 1971, Neoathousius Schimmel and Platia, 1991 and Solskyana Dolin, 1978 are all new synonymies of Limonius. A total of 84 new combinations are proposed: Nearctic: Elathous huguenini (Van Dyke, 1932) new combination; Gambrinus angulatus (Motschulsky, 1859) new combination; Gambrinus bicolor (Van Dyke, 1932) new combination; Gambrinus clypeatus (Motschulsky, 1859) new combination; Gambrinus confusus (LeConte, 1853) new combination; Gambrinus cribriceps (Van Dyke, 1943) new combination; Gambrinus crotchii (Horn, 1872) new combination; Gambrinus flavomarginatus (Knull, 1938) new combination; Gambrinus fulvipilis (Candèze, 1860) new combination; Gambrinus griseus (Beauvois, 1805) new combination; Gambrinus humidus (Lane, 1941) new combination; Gambrinus interstitialis (Melsheimer, 1846) new combination; Gambrinus lanchesteri (Lane, 1941) new combination; Gambrinus meridianus (Knull, 1947) new combination; Gambrinus mirus (LeConte, 1853) new combination; Gambrinus norahae (Al Dhafer, 2009) new combination; Gambrinus olentangyi (Knull, 1947) new combination; Gambrinus plebejus (Say, 1825) new combination; Gambrinus propexus (Candèze, 1860) new combination; Gambrinus rudis (Brown, 1933) new combination; Gambrinus rufihumeralis (Lane, 1941) new combination; Gambrinus seminudus (Van Dyke, 1932) new combination; Gambrinus shircki (Lane, 1965) new combination; Gambrinus sinuifrons (Fall, 1907) new combination; Gambrinus snakensis (Lane, 1965) new combination; Gambrinus stigma (Herbst, 1806) new combination; Gambrinus pictus (Van Dyke, 1932) new combination; Gambrinus ulkei (Horn, 1871) new combination; Gambrinus ursinus (Van Dyke, 1932) new combination; Gambrinus venablesi (Wickham, 1913) new combination; Limonius brevis (Van Dyke, 1932) new combination; Limonius sordidus (Van Dyke, 1932) new combination; Pheletes lecontei (Lane, 1971) new combination; Tetralimonius definitus (Ziegler, 1845) new combination; Tetralimonius humeralis (Candèze, 1860) new combination; Tetralimonius maculicollis (Motschulsky, 1860) new combination; Tetralimonius nimbatus (Say, 1825) new combination; Tetralimonius ornatulus (LeConte, 1857) new combination. Palearctic: Gambrinus elegans (Buysson, 1891) new combination; Gambrinus gibbosus (Platia and Gudenzi, 2006) new combination. Gambrinus henanensis (Schimmel, 2006) new combination; Gambrinus hinakurai (Kishii, 1998) new combination; Gambrinus katoi (Kishii, 2002) new combination; Gambrinus kawaharai (Kishii, 2002) new combination; Gambrinus kucerai (Schimmel, 2006) new combination; Gambrinus nanshanensis (Arimoto and Hiramatsu, 2013) new combination; Gambrinus naomii (Kishii, 1997) new combination; Gambrinus shaanxiensis (Schimmel, 2006) new combination; Gambrinus suturalis (Gebler, 1844) new combination; Gambrinus takabai (Kishii, 1997) new combination; Gambrinus violaceus (Müller, 1821) new combination; Gambrinus wittmeri (Chassain, 1998) new combination; Gambrinus yamato (Kishii, 1998) new combination; Gambrinus yujii (Arimoto, 2013) new combination; Gambrinus zhejiangensis (Schimmel, 2015) new combination; Limonius brancuccii (Schimmel and Platia, 1991) new combination; Limonius decorus (Gurjeva, 1975) new combination; Limonius exiguus (Schimmel and Platia, 1991) new combination; Limonius hartmanni (Schimmel, 1998) new combination; Limonius hiermeieri (Schimmel and Platia, 1991) new combination; Limonius hirtus (Dolin, 1978) new combination; Limonius hubeiensis (Kishii and Jiang, 1996) new combination; Limonius kubani (Schimmel, 1996) new combination; Limonius loebli (Schimmel and Platia, 1991) new combination; Limonius longicornis (Schimmel and Platia, 1991) new combination; Limonius macedonicus (Cate and Platia, 1989) new combination; Limonius marginellus brusteli (Leseigneur, 2004) new combination; Limonius manaliensis (Schimmel and Platia, 1991) new combination; Limonius miandamensis (Schimmel and Platia, 1991) new combination; Limonius minusculus (Schimmel and Platia, 1991) new combination; Limonius nigronitidus (Han and Lee, 2012) new combination; Limonius platiai (Mertlik, 1996) new combination; Limonius pseudopilosus (Platia and Gudenzi 1985) new combination; Limonius recticornis (Schimmel and Platia, 1991) new combination; Limonius riesei (Platia, 1988) new combination; Limonius rusticus (Schimmel and Platia, 1991) new combination; Limonius schurmanni (Platia and Gudenzi, 1998) new combination; Limonius sinensis (Schimmel and Platia, 1994) new combination; Limonius singularis (Schimmeland Platia, 1991) new combination; Limonius stapfi (Schimmel, 2007) new combination; Limonius turcicus (Platia, 2004) new combination; Limonius wittmeri (Schimmel and Platia, 1991) new combination; Tetralimonius quercus (Olivier, 1790) new combination; Tetralimonius reitteri (Gurjeva, 1976) new combination. The following 12 North American species are removed from synonymy and recognized as valid species: Gambrinus interstitialis (Melsheimer, 1846) status resurrected; Gambrinus propexus (Candèze, 1860) status resurrected; Gambrinus shircki (Lane, 1965) status resurrected; Gambrinus snakensis (Lane, 1965) status resurrected; Gambrinus ulkei (Horn, 1871) status resurrected; Limonius anceps LeConte, 1853 status resurrected; Limonius dubitans LeConte, 1853 status resurrected; Limonius infuscatus Motschulsky, 1859 status resurrected; Limonius pilosulus Candèze, 1891 status resurrected; Limonis semianeus LeConte, 1853 status resurrected. Tetralimonius humeralis (Candèze, 1860) status resurrected; Tetralimonius maculicollis (Motschulsky, 1860) status resurrected. New replacement names are proposed for three homynyms: Limonius schimmeli Etzler new name for Neoathousius ferrugineus Schimmel and Platia, 1991; Elathous malatyanus Etzler new name for Elathous bicolor Platia, 2010, not Elathous bicolor (LeConte, 1853); and Microdesmes carteri Etzler new name for Limonius angulatus Carter, 1939 (= Microdesmes angulatus). Limonius kondratieffi Al Dhafer, 2009 is a new synonymy of Elathous bicolor (LeConte, 1853). A key to genera, generic descriptions, notes on species, and definitions of important characters are provided.